Workshop Penyusunan Instrumen Angket Kinerja Guru, Lingkungan Kerja, Work Engagement, dan Self Efficacy dalam Melatih Keterampilan Penyusunan Instrumen Mahasiswa - Wawan Samudera (Jurnal Pendidik Indonesia (JPIn), 2021)
The instrument is a measuring tool of a research conducted. The existence of an instrument is something that cannot be separated from a research. Because what is the topic of discussion in research will certainly be contained in the instrument. The purpose of implementing this service is for students to be able to explore their abilities in compiling various research instruments in accordance with the field of science they are occupied with. The approach method used is coaching class. The results obtained through the implementation of this service are knowledge about the importance of knowing the pattern of preparing research instruments which in the end will certainly ease the process of solving various cases in everyday life, even in their respective departments